주택임대차 계약의 갱신에 관한 고찰 - 노현숙; Roh Hyeon Sook (감정평가학 논집, 2024)
이 논문은 주택임대차보호법상의 계약갱신과 묵시적 갱신, 소득세법 시행령에 따른 상생 임대제도 등 국내 주택임대차 계약의 갱신 제도에 관하여 살펴보고, 주택임대차 계약 갱신 규정들의 문제점을 검토하며 개선 방향을 살펴본다. 주택임대차 계약의 갱신 제도로는 주택임대차보호법상의 계약갱신요구권에 의한 계약갱신 및 묵시적 갱신과 소득세법 시행령상의 상생 임대제도에 따른 갱신 등을 들 수 있고, 이 제도들은 주택 임대차에 적용되는 대표적인 갱신의 형태이지만 적용상 불합리한 부분들이 발견된다. 주택임대차 계약의 갱신과 관련한 규정들은 임차인의 보호에 중점을 두어 임차인의 거주 안전성을 보장하고자 한 규정들이지만, 임차인의 거주 안전성 및 권리의 강화로 인하여 임대인의 권리가 과도하게 침해되거나 임대인과 임차인 권리가 지나치게 불평등하게 다루어지기도 한다. 임대인에게 초래된 불이익은 결과적으로 임차인에게 전가되거나 임대인과 임차인 간 원만하지 않은 관계를 조성하고 임대차시장의 불안정한 요인이 되어, 임차인을 보호하기 위한 원래의 취지에 상반되는 결과가 발생할 수 있고 종국적으로 임차인의 피해로 귀결될 수 있다. 계약갱신요구권에 의한 계약갱신과 묵시적 갱신 및 상생 임대제도 상의 갱신 규정의 불합리한 부분을 개선하여 임대인과 임차인이 상호 납득할 수 있는 합리적인 내용으로 보완될 필요가 있다. This paper examines the domestic housing lease renewal agreements, covering renewal agreements based on the lessee’s right to request, implied renewal agreements, and renewal agreements under the win-win lease system. It also scrutinizes issues encountered in applying these regulations and explores potential avenues for improvement. Renewal agreements based on the right to request, implied renewal agreements, and renewal agreements under the win-win lease system are principal forms of renewal agreements in Korean housing leases. However, applying these three systems reveals unreasonable aspects. Regulations concerning housing lease renewal primarily aim to safeguard the lessees and ensure the security of their residences. Yet, there’s risk of landlord’s rights being excessively violated, leading to disproportionate treatment between landlords and lessees. Disadvantages caused to the lessor may ultimately affect lessees or introduce instability into the rental market, fostering unsatisfactory relationships between lessors and lessees. Ultimately, this unstable rental environment would harm the lessees. Thus, there is a pressing need to enhance the regulations on the renewal agreements, supplementing them with reasonable and equitable rules mutually acceptable to both the lessors and the lessees.